Nanoscale Potentiometry - Bakker, Eric; Pretsch, E. (Elsevier Science B.V., 2008)
Potentiometric sensors share unique characteristics that set them apart from other electrochemical sensors. Potentiometric nanoelectrodes have been reported and successfully used for many decades, and we review these developments. Current research chiefly focuses on nanoscale films at the outer or the inner side of the membrane, with outer layers for increasing biocompatibility, expanding the sensor response, or improving the limit of detection (LOD). Inner layers are mainly used for stabilizing the response and eliminating inner aqueous contacts or undesired nanoscale layers of water. We also discuss the ultimate detectability of ions with such sensors and the power of coupling the ultra-low LODs of ion-selective electrodes with nanoparticle labels to give attractive bioassays that can compete with state-of-the-art electrochemical detection.